Quality of fresh and cryopreserved semen and their influence on the rates of fertilization, hatching and quality of the larvae of Piaractus mesopotamicus - J. M. Galo; D. P. Streit-Junior; C. A. Oliveira; J. P. Povh; D. C. Fornari; M. Digmayer; R. P. Ribeiro (Brazilian Journal of Biology, 2018)
Abstract In this work, the seminal parameters of P. mesopotamicus were evaluated fresh and after cryopreservation, focusing on the sperm variables that affect the rates of fertilization, hatching and post-hatching parameters such as larval survival and morphology. The semen and oocytes from the animals were collected after extrusion, and seminal quality and oocyte fertilization were analyzed. Subsequently, a portion of each semen sample was cryopreserved and, after two days, the oocytes from three new females were fertilized with cryopreserved semen from the males. The analyzes showed that progressive motility, spermatic vigor, motility duration, number of normal sperm and secondary abnormalities were higher in fresh semen than in semen after thawing (P <0.0001). Similarly, fertilization and hatching rates and the percentage of normal and abnormal larvae in fertilized oocytes were higher when fresh semen was used (P <0.0001). The cryopreservation process affected the qualitative parameters of the semen of Piaractus mesopotamicus. The primary abnormality of spermatozoa was the main variable that influenced both fertilization and hatching rates, both in fresh and thawed semen. The second most important variable that influenced, particularly, thawed semen, was the spermatic vigor.